2014
DOI: 10.1073/pnas.1318367111
|View full text |Cite
|
Sign up to set email alerts
|

The oligonucleotide/oligosaccharide-binding fold motif is a poly(ADP-ribose)-binding domain that mediates DNA damage response

Abstract: Oligonucleotide/oligosaccharide-binding (OB) fold is a ssDNA or RNA binding motif in prokaryotes and eukaryotes. Unexpectedly, we found that the OB fold of human ssDNA-binding protein 1 (hSSB1) is a poly(ADP ribose) (PAR) binding domain. hSSB1 exhibits highaffinity binding to PAR and recognizes iso-ADP ribose (ADPR), the linkage between two ADPR units. This interaction between PAR and hSSB1 mediates the early recruitment of hSSB1 to the sites of DNA damage. Mutations in the OB fold of hSSB1 that disrupt PAR bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 56 publications
(68 citation statements)
references
References 53 publications
3
64
0
1
Order By: Relevance
“…Proteins that specifically sense and modulate the ADP-ribosylation signals often contain structurally distinct, evolutionary conserved ADP-ribose binding modules (Barkauskaite et al, 2013b;Zhang et al, 2014). The structure-function relationships, detailing the recognition of ADP-ribosylation, have been described only for three of these ADP-ribose binding modules: the poly(ADP-ribose)-binding zinc finger (PBZ), WWE domains, and the macrodomain.…”
Section: Protein Adp-ribosylationmentioning
confidence: 99%
“…Proteins that specifically sense and modulate the ADP-ribosylation signals often contain structurally distinct, evolutionary conserved ADP-ribose binding modules (Barkauskaite et al, 2013b;Zhang et al, 2014). The structure-function relationships, detailing the recognition of ADP-ribosylation, have been described only for three of these ADP-ribose binding modules: the poly(ADP-ribose)-binding zinc finger (PBZ), WWE domains, and the macrodomain.…”
Section: Protein Adp-ribosylationmentioning
confidence: 99%
“…Upon DNA damage induction, PARP1, the founding member of PARPs, rapidly detects DNA single-strand breaks (SSBs) or double-strand breaks (DSBs), and is activated for PAR synthesis at DNA lesions within a few seconds in response to DNA damage(Kim et al, 2005; Luo and Kraus, 2012). Moreover, our previous study suggests that the solo OB-fold motif is able to recognize iso-ADP-ribose, the linkage between two ADP-ribose unites (Zhang et al, 2014). Here, our results suggested that the tandem OB-folds of BRCA2 recognize DNA damage-induced PAR and target BRCA2 to DNA lesions.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Using nicotinamide adenine dinucleotide (NAD) as the donor, a group of enzymes, namely poly (ADP-ribose) polymerases (PARPs), catalyze this posttranslational modification by covalently linking ADP-ribose to protein targets and building the linear and branched chains of poly (ADP-ribose) (PAR). [5][6][7] Interestingly, recent studies suggest that PARylation occurs at the spindle apparatus during mitosis, [8][9][10] implying a novel function of PAR during mitosis.…”
Section: Introductionmentioning
confidence: 99%